2016
DOI: 10.1101/lm.042978.116
|View full text |Cite
|
Sign up to set email alerts
|

Reward retroactively enhances memory consolidation for related items

Abstract: Reward motivation has been shown to modulate episodic memory processes in order to support future adaptive behavior. However, for a memory system to be truly adaptive, it should enhance memory for rewarded events as well as for neutral events that may seem inconsequential at the time of encoding but can gain importance later. Here, we investigated the influence of reward motivation on retroactive memory enhancement selectively for conceptually related information. We found behavioral evidence that reward retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
169
4
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(197 citation statements)
references
References 26 publications
21
169
4
3
Order By: Relevance
“…Here, we show that mesolimbic activation may support memory consolidation not only by stabilizing processes within the hippocampus but also supporting post-encoding hippocampal interactions with cortical regions. This interpretation dovetails well with prior work from our laboratory associating rewardmemory benefits with post-encoding interactions between the hippocampus and sensory cortex , as well as generalization of consolidation-related memory benefits across sensory categories (Patil et al, 2017). Critically, our current findings and previous work do not directly measure mesolimbic dopamine activation, but rather induce behavioral contexts that have previously been associated with dopamine activation in rodent and human studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Here, we show that mesolimbic activation may support memory consolidation not only by stabilizing processes within the hippocampus but also supporting post-encoding hippocampal interactions with cortical regions. This interpretation dovetails well with prior work from our laboratory associating rewardmemory benefits with post-encoding interactions between the hippocampus and sensory cortex , as well as generalization of consolidation-related memory benefits across sensory categories (Patil et al, 2017). Critically, our current findings and previous work do not directly measure mesolimbic dopamine activation, but rather induce behavioral contexts that have previously been associated with dopamine activation in rodent and human studies.…”
Section: Discussionsupporting
confidence: 86%
“…Memory consolidation in this context refers to the strengthening of memory after encoding and prior to retrieval, often demonstrated as a resistance to forgetting over time. Behavioral studies have shown that memory enhancements of information encoded under reward motivation, which is thought to engage mesolimbic dopamine systems, only emerge after a significant delay (Murayama & Kitagami, 2014;Murayama & Kuhbandner, 2011;Patil, Murty, Dunsmoor, Phelps, & Davachi, 2017). Further, rodent studies show that reward and novelty-based enhancements rely on dopamine-mediated consolidation (Abraham, Neve, & Lattal, 2016;Li, Cullen, Anwyl, & Rowan, 2003a;Salvetti, Morris, & Wang, 2014;Takeuchi et al, 2016;Wang, Redondo, & Morris, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…showing that emotional associations generalize across a category and lead to enhanced 341 memory for the reinforced category of exemplars in adults (Dunsmoor et al, 2014(Dunsmoor et al, , 2012342 Kroes et al, 2017;Patil et al, 2017). However, we did find some evidence of increased correct 343 high-confidence memory judgements for both odor-paired stimuli and unreinforced stimuli of the 344 same category, relative to stimuli that were never reinforced.…”
Section: Discussion 315mentioning
confidence: 53%
“…Although other variants of category condition paradigms have also omitted expectancy ratings 362 and still observed memory facilitation effects (Patil et al, 2017), it is possible that this may have reduced the demand on participants' attention, attenuating their anticipatory responses. Another 364 reason that we may not have fully replicated prior studies is our use of a different primary 365 reinforcer.…”
Section: Discussion 315mentioning
confidence: 99%
See 1 more Smart Citation